Using Teammate to Improve Speaking Skill of 11th Grade Students - Sisvia, Sisvia; Mutia, Utin; Husnayaini, Ihda; Novrieta, Dina (EEdJ: English Education Journal, 2022)
This research was carried out to know the implementation of Teammate in improving students’ in speaking skill of procedure texts and to find out the significant difference between students' speaking ability of procedure texts using Teammate and Non-Teammate. The subjects of this study were students of class XI SMA Muhammadiyah. In this study, the researcher used a quantitative approach with a quasi-experimental design. The results showed that the post-test mean score in the experimental group was higher (68.66) compared to the average score in the control group (63.72). Meanwhile, the results of the independent sample test of students' post-test between the experimental and control groups, obtained t in the same variance assumed to be 3.229 and significant (2-tailed) was 0.000. Because the t obtained is greater than the t-table ((3.229>0.0845)) and significantly (2-tailed) lower than the calculation with a significant level (.000<0.05). Based on the facts above, it can be concluded that there is a significant difference between the samples, and Teammate Strategy improves students' speaking ability. Therefore, the results of this study are expected to contribute to the development of the teaching and learning process of English, especially for teaching and learning speaking skills